Models of interventions in the treatment of children with Autism Spectrum Disorder: a comparison between music therapy and equine therapy (Research, Society and Development, 2023)
Autistic Spectrum Disorder (ASD) is a neurodevelopmental disorder with a multifactorial nature, with great genetic, maternal and environmental influences that contribute to its pathogenesis, in addition, it also demonstrates a hereditary nature. ASD has characteristic symptoms that affect social interactions, behavior and, in some cases, balance, motor coordination and the individual's spatial and temporal perception. Assisted equine therapy and music therapy are two therapy models recurrently chosen for the treatment of autistic children and adolescents, seeking to improve communication and social skills of these children. This work aims to compare the efficiency of music therapy and equine therapy as methods of therapeutic intervention in autism. This is an exploratory and integrative bibliographic review study, which used the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMed), EbscoHost and Google Scholar as a database, using for research the descriptors “autism”, “equine therapy”, “music therapy” and “children”, in English and Portuguese. All the articles found mentioned a positive reaction in the children who went through the therapeutic processes, showing a significant improvement in their social interaction skills and communication skills. Music therapy proved capable of improving emotional understanding, as well as helping with school development. Equine therapy has the ability to cause a great evolution in the physical aspect of children, improving muscle tone, memory, balance and temporal space perception, in addition to a positive behavioral development in the observed children.